2003
DOI: 10.1081/pdt-120017518
|View full text |Cite
|
Sign up to set email alerts
|

Medium Chain Triglycerides as Vehicle for Palatable Oral Liquids

Abstract: Aqueous liquid formulations of efavirenz, a nonnucleoside inhibitor of reverse transcriptase, have prolonged burning (peppery) taste. Medium-chain triglycerides (MCT) was used as the vehicle to mask the taste and obtain palatable oral liquid formulations containing 20 mg/mL efavirenz. The use of MCT for enhancement of palatability and stability is recommended for drugs that show high solubility and partitioning in this vehicle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…The three treatments were: 6·2 g/d n- 3 PUFA (3·7 g EPA and 2·5 g DHA), 3·1 g/d n- 3 PUFA (1·8 g EPA and 1·3 g DHA) (INCROMEGA TM TG4030; Croda International Plc) and placebo (CRODAMOL TM GTCC medium chain TAG; Croda International Plc) (Table 2). CRODAMOL TM GTCC was chosen as it is readily oxidised in the liver so has little impact on human health-related biomarkers ( 29 , 30 ) . Measurements were taken at days 0 and 21 of each treatment period.…”
Section: Methodsmentioning
confidence: 99%
“…The three treatments were: 6·2 g/d n- 3 PUFA (3·7 g EPA and 2·5 g DHA), 3·1 g/d n- 3 PUFA (1·8 g EPA and 1·3 g DHA) (INCROMEGA TM TG4030; Croda International Plc) and placebo (CRODAMOL TM GTCC medium chain TAG; Croda International Plc) (Table 2). CRODAMOL TM GTCC was chosen as it is readily oxidised in the liver so has little impact on human health-related biomarkers ( 29 , 30 ) . Measurements were taken at days 0 and 21 of each treatment period.…”
Section: Methodsmentioning
confidence: 99%
“…A commercial medium-chain triglyceride solution of EFV has shown lower oral bioavailability than the solid form. Preclinical studies indicated that the encapsulation of EFV in poloxamine micelles increases the C max and the area-under-thecurve (AUC) [11] compared to the conventional triglyceride-based liquid formulation [16]. However, when the release profile was tested in vitro using the dialysis membrane method in intestine-like mimicking medium over 24 h, only 40% of the drug was released from the micellar reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to solid dosage forms, the pharmaceutical development of oral liquid dosage forms of EFV for use in pediatrics or in adults with difficulty in swallowing is challenging. Not only is the solubility of EFV very low, but it imparts a strong and prolonged burning sensation to the mouth and throat when incorporated in water containing liquid formulations (2). CDs can be used to reduce the GI irritation and unpleasant taste of drugs (12).…”
Section: Introductionmentioning
confidence: 99%
“…1). It is a crystalline lipophilic solid (log octanol water partition coefficient of 5.4) with a molecular mass of 315.68 and an aqueous solubility of 9.0 μg/ml (1,2). This is a class II drug (low solubility, high permeability) according to the biopharmaceutical classification system guidance by the Food and Drug Administration (3,4).…”
Section: Introductionmentioning
confidence: 99%